Dynamics of labor demand: Evidence from plant-level observations and aggregate implications. Issue 1 (March 2015) - Cooper, Russell; Haltiwanger, John; Willis, Jonathan L.
Abstract: This paper studies the dynamics of labor demand at the plant level to quantify labor adjustment costs. At the plant level, in contrast to time-series observations, the correlation of hours and employment growth is negative while hours and employment growth are about equally volatile. We specify and estimate the parameters of a plant-level dynamic optimization problem using simulated method of moments to match these plant-level observations. Our findings indicate that non-convex adjustment costs are critical for explaining plant-level observations on hours and employment adjustment. Abstract : Highlights: This paper studies the dynamics of labor demand at the plant level to quantify labor adjustment costs. We specify and estimate the parameters of a plant-level dynamic optimization problem using simulated method of moments to match plant-level observations. Our findings indicate that non-convex adjustment costs are critical for explaining plant-level observations on hours and employment.